Babylonian Astronomy II. The Thirty-six Stars - van der Waerden, B. L.
1. Hilprecht’s Nippur Text — 2. The Stars as Indicators of Seasons in Egypt and Greece — 3. “The Three Stars Each” — 4. The Stars of Elam, Akkad and Amurru — 5. Which Stars Were Meant — 6. Comparison between the Astrolabes and mulapin — 7. The Paths of the Stars of Enlil, Anu, and Ea — 8. The Numbers on the Circular Astrolabe — 9. The Thirty-six Stars in mulapin — 10. The Date and Place of Observation — 11. Astronomical Science in the Great Omen Period — 12. Astrolabe B, Star Mythology, and Diodorus — 13. The Sun’s Path in mulapin — 14. The Twelve Zodiacal Signs.